Ticking and talking in the brainstem satiety centre: Circadian timekeeping and interactions in the diet-sensitive clock of the dorsal vagal complex - Chrobok, Lukasz; Ahern, Jake; Piggins, Hugh D. (Frontiers in Physiology, 2022)
The dorsal vagal complex (DVC) is a key hub for integrating blood-borne, central, and vagal ascending signals that convey important information on metabolic and homeostatic state. Research implicates the DVC in the termination of food intake and the transition to satiety, and consequently it is considered a brainstem satiety centre. In natural and laboratory settings, animals have distinct times of the day or circadian phases at which they prefer to eat, but if and how circadian signals affect DVC activity is not well understood. Here, we evaluate how intrinsic circadian signals regulate molecular and cellular activity in the area postrema (AP), nucleus of the solitary tract (NTS), and dorsal motor nucleus of the vagus (DMV) of the DVC. The hierarchy and potential interactions among these oscillators and their response to changes in diet are considered a simple framework in which to model these oscillators and their interactions is suggested. We propose possible functions of the DVC in the circadian control of feeding behaviour and speculate on future research directions including the translational value of knowledge of intrinsic circadian timekeeping the brainstem.